National report on traineeships : the Netherlands - Hensen-Reifgens, Kristina Alice [Verfasser]; Frommberger, Dietmar [Verfasser] (My University, 2012)
"Traineeships ('stages'; 'stagelopen'; 'praktijkvorming'; 'beroepspraktijkvorming' (BPV); 'bpv-plaatsen') are an essential element of general, vocational and higher education in the Netherlands. In many programmes traineeships are an integral part of the curriculum. This is particular the case for the following sectors of vocational and higher education and training: Preparatory senior secondary vocational education (voorbereidend middelbaar beroepsonderwijs - VMBO) - a component of fulltime compulsory general education/lower secondary education. Senior secondary vocational education (middelbaar beroepsonderwijs - MBO) - the main part of vocational education and training in the Netherlands. Vocational/professional higher education (hoger beroepsonderwijs, HBO), which forms the bridge between vocational education and training and higher education. The main information presented in this study refers to these three elementary areas of the public system of vocational education, training and higher education in the Netherlands." (Autorenreferat, BIBB-Doku)
Keywords: S 1.6.1 Praktika; G 1.3.2.2 Übergänge; I 2.2.1 Westeuropa; Praktikum; Berufsvorbereitung; Berufseinmündung; Niederlande